1998
DOI: 10.1103/physrevlett.81.3511
|View full text |Cite
|
Sign up to set email alerts
|

Strong Tunneling in the Single-Electron Box

Abstract: We study strong tunneling (i.e. transmission h/e 2 RT ≫ 1) in the single-electron box with many transverse modes at zero temperature. We develop a new renormalization group method which includes all charge states and requires no initial or final energy cutoff. We determine the ground-state energy, the average charge and the renormalized charging energy. The covered range for the coupling constant and the gate voltage is much increased in comparison to recent perturbative approaches, poor man scaling methods an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…This idea has been applied to the single-electron box [10], coupled metallic islands [19], and the one-dimensional Polaron problem [20]. In the first two cases very good results have been obtained, even comparable to very time-consuming QMCsimulations.…”
Section: Discussionmentioning
confidence: 99%
“…This idea has been applied to the single-electron box [10], coupled metallic islands [19], and the one-dimensional Polaron problem [20]. In the first two cases very good results have been obtained, even comparable to very time-consuming QMCsimulations.…”
Section: Discussionmentioning
confidence: 99%
“…The first and second diagram in Fig. 7 represent a correction to j − , 19) whereas the third and fourth diagram represent an additional renormalization of the distribution function for right moving fermions, which can be represented by a change in the relation between toG R and G R ,…”
Section: B Large Number Of Channelsmentioning
confidence: 99%
“…The other theoretical approach starts from an effective theory in which the primary dynamic variables are the potential differences between the quantum dot and the electrodes. 9 This approach has mainly been used to study metal grains coupled to the reservoirs via tunnel barriers with many channels, 10,11,12,13,14,15,16,17,18,19,20 , but recently it has been applied to semiconductor quantum dots, both without 21,22,23 and with 24 coherent scattering of electrons from inside the quantum dot. The general conclusions of both approaches are the same: For the incoherent case and ideal point contacts (no backscattering in the contact), it was found that all charge quantization effects completely vanishes.…”
Section: Introductionmentioning
confidence: 99%
“…This problem has been extensively investigated by instanton methods 14,15,16,17 , by RG methods 8,9,18 , and by Monte Carlo (MC) methods 9,10,19 . All methods show that B c increases exponentially with the dissipation strength α, i.e.…”
mentioning
confidence: 99%